Efectos de enmiendas con biochard en el desarrollo vegetativo de musa spp. en un suelo franco-arcilloso - Sotamba Guaman, Silvia Estefania (Machala : Universidad Técnica de Machala, 2022)
The soil is the decomposition of rock material in which it is made up of 45% minerals, 25% gas, 25% water, 5% organic matter, for the development of crops and their fertility or optimal properties depends on agricultural productivity and food security. Soil fertility is the ability to sustain vegetative plant growth and optimize crop yields. This can be enhanced by organic and inorganic fertilizers that provide the necessary nutrients to the soil, improve soil fertility and crop production, while reducing environmental impact. The available raw material of biochar can be an important alternative, the use of this material has the ability to improve the physical-chemical characteristics of the soil and increases the productivity of crops, also contributing to carbon sequestration, reducing the use of fertilizers , which makes it a tool for mitigating climate change, having the ability to restore the natural balance of the soil and improve crop yields through better retention of water and nutrients, which leads to greater tolerance to drought and higher yields in crop production due to increased soil fertility. With the aforementioned, the research work aims to analyze the effectiveness of the different components of biochar + silicon oxide + agricultural gypsum on the growth of banana plants (Cavendish) in combination with more biol as a phytoregulator source, by measuring several agronomic parameters of the plant of both the mother and the son, in which the chemical factors of the soil, texture, pH, organic matter and the weight of the roots were evaluated. A completely randomized design was carried out on a banana farm with the clone variety Cavendish Av. Panamericana Km. 5.7 Vía Machala - Pasaje in the Province of El Oro, delimiting five plots for the trial, using 4 treatments and a control or witness, each treatment with 10 repetitions: T1 (25g Cocoa Biochar + 50g Silicon), T2 (50g Cocoa Biochar + 50g Silicon), T3 (20g Banana Biochar + 50g Silicon), T4 (30g Banana Biochar + 50g Silicon) and the control treatment (50g Silicon) .the variables to be determined were: Number of leaves of the mother, number of leaves of the son, thickness of the pseudostem-son, height of the son, at the end a soil analysis was carried out to determine the percentage of its roots; the percentage of texture, organic matter and pH were also made. The effects that appeared from the different insidio treatments efficiently in foliar emission which is positive due to the photosynthetic load of the plant is greater, in the first variable of leaf number of the mother plant there was a non-considered foliar increase of the which T4 has the best efficiency; For the following variable number of leaves in the daughter plant, a good increase in foliar emission was obtained with similar means (11.9 leaves) between treatments T0-T2 and treatments T1-T3 (11 leaves). In the pseudostem-son variable, its thickness increased, presenting T4 followed by T2-T1 or being the highest mean, for the height of the son decreasing in the T0 treatment. In root weight, the best treatment was T3 and T0 with a higher biomass (1159.50g-757.00g) than the other treatments, the highest percentage of Organic Matter was obtained from T3 and T1, unlike the others; while the pH measurement responded to a great change in the treatments, having a slightly alkaline pH, of which the highest values ​​were in the treatments T1 and T2. The combination of the different doses responded positively and efficiently in the development of the banana plants, intervening in all the variables to be measured with very noticeable results represented in the study of this research, obtaining better results in the T1 treatments (25g Biochar Cocoa + 50g of silicon + Biol) and T4 (30g Banana Biochar + 50g Silicon + Biol)
El suelo es la descomposición del material roca en el cual está constituido por el 45% de Minerales ,25%Gas ,25% Agua,5%Materia orgánica , para el desarrollo de los cultivos y de su fertilidad o propiedades optimas depende la productividad agrícola y la seguridad alimentaria. La fertilidad del suelo es la capacidad de sostener el crecimiento vegetativo de las plantas y optimizar el rendimiento de los cultivos. Ello puede potenciarse por medio de fertilizantes orgánicos e inorgánicos que aportan los nutrientes necesarios que aporte al suelo, mejoran la fertilidad del suelo y la producción de cultivos, al mismo tiempo reduciendo el impacto medioambiental. La materias prima disponibles del biocarbon puede ser una alternativa importante , la utilización de este material tiene la capacidad de mejorar las características físico-químicas de suelo y aumenta la productividad de los cultivos, contribuyendo además al secuestro de carbono, la reducción del uso de fertilizantes, por lo que lo convierte en una herramienta para la mitigación al cambio climático, teniendo la capacidad de restaurar el equilibrio natural del suelo y mejorar el rendimiento de los cultivos mediante una mejor retención de agua y nutrientes, lo que conlleva una mayor tolerancia a la sequía y un mayor rendimiento en la producción de cultivos por el aumento de la fertilidad del suelo. Con lo antes mencionado el trabajo de investigación tiene como objetivo analizar la eficacia de los diferentes componentes de biochar + óxido de silicio + yeso agrícola sobre el crecimiento de plantas de banano (Cavendish) en combinación de más biol como fuente fitorregulador, mediante la medición de varios parámetros agronómicos de la planta tanto de la madre como del hijo, en el cual se evaluó los factores químicos del suelo, Textura, pH, materia orgánica y el peso de las raíces. Se realizo un diseño completamente al azar en una finca bananera con variedad de clon Cavendish Av. Panamericana Km. 5.7 Vía Machala - Pasaje en la Provincia de El Oro, delimitando cinco parcelas para el ensayo, estableciendo 4 tratamientos y un control o testigo, cada tratamiento con 10 repeticiones: T1 (25g Biochar Cacao+50g Silicio), T2(50g Biochar de Cacao+50gSilicio),T3(20g Biochar Banano+50gSilicio),T4(30g Biochar Banano+50gSilicio) y el tratamiento testigo (50g Silicio) .las variables a determinase fueron: Número de hojas de la madre, número de hojas del hijo, grosor del pseudotallo-hijo, altura del hijo, al final se realizó un análisis del suelo para determinar el porcentaje de sus raíces ; también se realizó el porcentaje de Textura ,materia orgánica y pH. Los efectos que presentaron de los diferentes tratamientos insidio de manera eficiente en la emisión foliar lo cual es positivo por la carga fotosintética de la planta es mayor, en la primera variable de numero de hoja de la planta madre hubo un considerado aumento foliar de la cual el T4 presento la mejor eficiencia; para la siguiente variable número de hojas en la planta hijo obtuvieron buen aumento de la emisión foliar con medias semejantes (11,9hojas) entre los tratamientos T0-T2y los tratamientos T1-T3 (11,hojas). En la variable del pseudotallo-hijo su grosor aumento presentando T4 seguido del T2-T1 o siendo la mayor media, para la altura del hijo disminuyendo en el tratamiento T0. En el peso de raíces el mejor tratamiento fue el T3 y T0 con una biomasa mayor (1159,50g-757,00g) a los demás tratamientos, el mayor porcentaje de Materia Orgánica se obtuvo del T3y T1 a diferencia de los demás; mientras que la medición del pH respondió un gran cambio en los tratamientos teniendo pH ligeramente alcalinos de las cuales los valores mayores fueron en los tratamientos T1 y T2. La combinación de las diferentes dosis respondió de manera positiva y eficiente en el desarrollo de las plantas de banano, interviniendo en todas las variables a medir con resultados muy notorios representados en el estudio de esta investigación obteniendo como mejores resultados en los tratamientos T1 (25g Biochar Cacao + 50g de silicio + Biol) y T4(30g Biochar Banano+50gSilicio+Biol)
Keywords: MATERIA; PRIMA; SUELO; NUTRIENTES